Functionalization of Pyrene To Prepare Luminescent Materials—Typical Examples of Synthetic Methodology. Issue 34 (8th July 2016) - Feng, Xing; Hu, Jian‐Yong; Redshaw, Carl; Yamato, Takehiko
Abstract: Pyrene‐based π‐conjugated materials are considered to be an ideal organic electro‐luminescence material for application in semiconductor devices, such as organic light‐emitting diodes (OLEDs), organic field‐effect transistors (OFETs) and organic photovoltaics (OPVs), and so forth. However, the great drawback of employing pyrene as an organic luminescence material is the formation of excimer emission, which quenches the efficiency at high concentration or in the solid‐state. Thus, in order to obtain highly efficient optical devices, scientists have devoted much effort to tuning the structure of pyrene derivatives in order to realize exploitable properties by employing two strategies, 1) introducing a variety of moieties at the pyrene core, and 2) exploring effective and convenient synthetic strategies to functionalize the pyrene core. Over the past decades, our group has mainly focused on synthetic methodologies for functionalization of the pyrene core; we have found that formylation/acetylation or bromination of pyrene can selectly lead to functionalization at K‐region by Lewis acid catalysis. Herein, this Minireview highlights the direct synthetic approaches (such as formylation, bromination, oxidation, and de‐ tert ‐butylation reactions, etc.) to functionalize the pyrene in order to advance research on luminescent materials for organic electronic applications. Further, this article demonstrates that the future direction of pyrene chemistry is asymmetric functionalization of pyrene for organic semiconductor applications and highlights some of the classical asymmetric pyrenes, as well as the latest breakthroughs. In addition, the photophysical properties of pyrene‐based molecules are briefly reviewed. To give a current overview of the development of pyrene chemistry, the review selectively covers some of the latest reports and concepts from the period covering late 2011 to the present day. Abstract : Pepping up pyrene : This Minireview highlights direct synthetic approaches to functionalize the pyrene at the active sites (the 1‐, 3‐, 6‐, and 8‐positions), the K‐region (the 4‐, 5‐, 9‐, and 10‐positions), and the nodal plane (the 2‐ and 7‐positions), in order to advance research on luminescent materials for organic electronic applications. Further, this article demonstrates the future direction of pyrene chemistry for organic semiconductor application and highlights some classical asymmetric pyrenes, as well as the latest breakthroughs.